Inhibition of ROS-mediated activation Src-MAPK/AKT signaling by orientin alleviates H 2 O 2 -induced apoptosis in PC12 cells - Qi, Shimei; Feng, Zunyong; Li, Qiang; Qi, Zhilin; Zhang, Yao (Drug design, development and therapy, 2018)
Reactive oxygen species (ROS) are considered a direct cause of neurodegenerative diseases (NDDs). Drugs developed to target ROS are effective for the treatment of NDDs. Orientin is a pyrone glucoside extracted from , and it exhibits many pharmacological activities. In this study, we aimed to determine whether orientin could relieve hydrogen peroxide (H O )-induced neuronal apoptosis and to investigate the specific target of orientin. In this study, the neuroprotective effect and its possible mechanisms of orientin in mouse pheochromocytoma cell line (PC12) cells stimulated by H O , establishing an oxidative stress model, were investigated. And we further tested the role of ROS in the neuroprotective effects of orientin. Orientin (5-100 µg/mL) did not cause toxicity in PC12 cells but significantly decreased H O -induced reduction in PC12 cell viability, cell apoptosis rates, and nuclear condensation. It also inhibited the activation of caspase-3 and degradation of poly(ADP-ribose) polymerase (PARP). Under the stimulation of H O , MAPKs (ERK, JNK, and p38), AKT, and Src signaling proteins in PC12 cells were activated in a time-dependent manner. The application of inhibitors that were specific for MAPKs, AKT, and Src effectively alleviated H O -induced cell apoptosis. In addition, the Src inhibitor decreased the activation of MAPKs and AKT signaling. More importantly, orientin effectively decreased H O -induced phosphorylation of MAPKs, AKT, and Src signaling proteins. Finally, we confirmed that orientin effectively inhibited H O -induced accumulation of ROS in cells. In addition, ROS inhibitors blocked the Src-MAPKs/AKT signaling pathway-dependent cell apoptosis stimulated by H O . These results indicate that alleviation of H O -induced cell apoptosis by orientin is Src-MAPKs/AKT dependent. Overall, our study confirms that orientin alleviates H O -induced cell apoptosis by inhibiting the ROS-mediated activation of Src-MAPKs/AKT signaling.